Association between cyclic variation in the heart rate index and biomarkers of neurodegenerative diseases in obstructive sleep apnea syndrome: A pilot study. (April 2022) - Tsai, Cheng-Yu; Liu, Yi-Shin; Majumdar, Arnab; Houghton, Robert; Lin, Shang-Yang; Lin, Yin-Tzu; Ho, Shu-Chuan; Cheng, Wun-Hao; Liu, Wen-Te; Wu, Dean; Lee, Hsin-Chien; Kuan, Yi-Chun; et al.
Highlights: This study indicated a significant and positive correlation between the T-Tau protein level in plasma and a novel sleep disorder index measured at home. The severe obstructive sleep apnea syndrome patients classified by home-based sleep disorder index demonstrated significantly higher T-Tau protein levels than non-severe patients. The novel sleep disorder index determined at home were lower than those obtained in the hospital. Abstract: Purpose: Obstructive sleep apnea syndrome (OSAS) has mostly been examined using in-laboratory polysomnography (Lab-PSG), which may overestimate severity. This study compared sleep parameters in different environments and investigated the association between the plasma levels of neurochemical biomarkers and sleep parameters. Methods: Thirty Taiwanese participants underwent Lab-PSG while wearing a single-lead electrocardiogram patch. Participants' blood samples were obtained in the morning immediately after the recording. Participants wore the patch for the subsequent three nights at home. Sleep disorder indices were calculated, including the apnea-hypopnea index (AHI), chest effort index, and cyclic variation of heart rate index (CVHRI). The 23 eligible participants' derived data were divided into the normal-to-moderate (N-M) group and the severe group according to American Association of Sleep Medicine (AASM) guidelines (Lab-PSG) and the recommendations of a previous study (Rooti Rx). Spearman's correlation was used to examine the correlations between sleep parameters and neurochemical biomarker levels. Results: The mean T-Tau protein level was positively correlated with the home-based CVHRI ( r  = 0.53, p  < 0.05), whereas no significant correlation was noted between hospital-based CVHRI and the mean T-tau protein level ( r  = 0.25, p  = 0.25). The home-based data revealed that the mean T-Tau protein level in the severe group was significantly higher than that in the N-M group (severe group: 24.75 ± 6.16 pg/mL, N-M group: 19.65 ± 3.90 pg/mL; p  < 0.05). Furthermore, the mean in-hospital CVHRI was higher than the mean at-home values (12.16 ± 13.66 events/h). Conclusion: Severe OSAS patients classified by home-based CVHRI demonstrated the higher T-Tau protein level, and CVHRI varied in different sleep environments.